The legacy of history in Russia and the new states of Eurasia / editor, S. Frederick Starr. - Starr, S. Frederick. (The international politics of Eurasia, 1994)
"This ambitious ten-volume series develops a comprehensive analysis of the evolving world role of the post-Soviet successor states. Each volume considers a different factor influencing the relationship between internal politics and international relations in Russia and the western and southern tiers of newly independent states. The contributors were chosen not only for their recognized expertise but also to ensure a stimulating diversity of perspectives and a dynamic mix of approaches."--BOOK JACKET.